Treatment of a Multitraumatized Tortured Refugee Needing an Interpreter with Exposure Therapy. (9th January 2013) - Jensen, Bo Søndergaard
Abstract : This paper described the application and feasibility of exposure therapy treatment (ET) for posttraumatic stress disorder (PTSD) in a multitraumatized tortured refugee with chronic PTSD and depression, in need of an interpreter. The patient received 26 one-hour sessions of ET involving exposure to his trauma-related memories. Symptoms of PTSD, depression, and anxiety were assessed at pre- and posttreatment and 3-, 6-, and 12-month followup with the Harvard Trauma Questionnaire (HTQ-R), PTSD Symptom Scale-Self Report (PSS-SR), Major depression inventory (MDI), and Beck Anxiety Inventory (BAI). Treatment led to a significant improvement across all measures of posttraumatic stress disorder, anxiety, and depression, and the improvement was maintained at the 12-month follow-up. The results from this case study provide further preliminary evidence that ET may be effective in treating multi-traumatized torture survivors who are refugees and in need of an interpreter, despite the additional stressors and symptoms complexity experienced by tortured refugees.